Negotiating Barriers to Learning, Part 1 - Herbert, Susan (Daily Express, 2007)
Part 1 of this article discusses barriers to learning that are experienced by students, especially those of low socio-economic status, and suggests strategies for negotiating these barriers
Keywords: Primary school students; Learning difficulties; Low income groups; Socioeconomic status; Educational strategies